Temperature Profile and Thermocline Thickness Evaluation of a Stratified Thermal Energy Storage Tank - Waluyo, Joko; A. Majid, M. Amin (2010)
Determination of thermocline thickness requires a continuous profile of temperature distribution. Difficulty in determining thermocline thickness arises for the case of discrete temperature data, since the profile formed could not be used to estimate the thermocline thickness. This paper discusses a practical method for formulation of thermocline thickness of stratified thermal energy storage. Curve fitting by iterative method was adopted to identify the functions which could represent the S-curve of temperature distribution. Based on the functions, thermocline thickness was formulated using functional relationship of temperature profile. Results identified two functions which could represent S-curve of temperature distribution, namely sigmoid dose response (SDR) and four parameter sigmoid (FPS) functions. Both functions were observed to well fit the temperature distributions having coefficient determination more than 0.99. Based on evaluations the formulations were capable to be utilized for evaluation of thermocline thickness of the stratified TES. The methods offer an advantage to obtain an exact value of thermocline thickness.